(untitled) (PAAN Journal, 2026)
This article examines the possible ways in which the use of artificial intelligence (AI) can transform Nepal’s public sector digital payment systems by enhancing security, efficiency, and inclusivity. Using cases from India (UPI), China (Alipay), Singapore (PayNow), Sweden, and Estonia, it demonstrates how AI-powered fraud mitigation, risk scoring, and digital identification networks enhance our nation’s payment infrastructures. Although adoption of digital payments in Nepal is increasing with the number of e-wallet accounts reach 23.5 million by 2024, from 6.2 million in 2020 (NRB, 2023; NRB, 2025), systemic weaknesses remain, as a result of rising cybercrime and Nepal’s low AI readiness position (150th globally) (Oxford Insights, 2023). The paper recommends a strategic approach for an AI in Nepal comprising real time fraud analytics, chatbot based support, adaptive scoring, and federated detection models. It also recommends strengthening cybersecurity laws, implementing a universal e-ID, and enabling data sharing through open APIs. Grounded in international best practices, this roadmap presents a forward looking vision for building a secure, inclusive, and AI-driven digital payment ecosystem in Nepal.